2016
DOI: 10.3389/fnins.2016.00455
|View full text |Cite
|
Sign up to set email alerts
|

Histological Basis of Laminar MRI Patterns in High Resolution Images of Fixed Human Auditory Cortex

Abstract: Functional magnetic resonance imaging (fMRI) studies of the auditory region of the temporal lobe would benefit from the availability of image contrast that allowed direct identification of the primary auditory cortex, as this region cannot be accurately located using gyral landmarks alone. Previous work has suggested that the primary area can be identified in magnetic resonance (MR) images because of its relatively high myelin content. However, MR images are also affected by the iron content of the tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that myelin is the predominant source of MR contrast in T1‐weighted and T2‐weighted images (Bock, Kocharyan, Liu, & Silva, ; Eickhoff et al, ; Laule et al, ; Wallace et al, ), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, ). Although, other studies have questioned the sensitivity of the T1‐w/T2‐w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1‐w/T2‐w image (Arshad et al, ; Righart et al, ; Uddin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes tended to be most pronounced in anatomical areas known to be affected in AD such as the interior parietal lobule and precuneus, and were associated with higher levels of the neuronal injury marker tau and worse cognition. Wallace et al, 2016), and by using the ratio of these images the contrast sensitivity to detect myelin content is increased further due to attenuation of the shared intensity biases (Glasser & Van Essen, 2011). Although, other studies have questioned the sensitivity of the T1-w/T2-w ratio for myelin content, and argued that it is likely not the only factor contributing to the T1-w/T2-w image (Arshad et al, 2017;Righart et al, 2017;Uddin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, is there spatial correspondence between auditory cortical anatomy, as measured by the local change in R1-estimated myelination, and the strength of the fMRI-assessed strength of relative frequency selectivity? Post-mortem Gallyas staining to establish human myeloarchitecture reveals considerable variability in auditory cortical myelination that is associated with MRI signal change in the same brain (Wallace et al, 2016). Likewise, variation in cortical myelination estimated using T1/T2 ratio approaches also appears to correspond spatially with some functional variation in the superior temporal lobe (Glasser et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…This results in a more direct relationship with specific microstructural components, although not a trivial one-to-one relationship. Studies on the contribution of myelin and iron to different relaxation time constants showed that maps of R1 (¼1/T1) values are mainly dominated by myelin concentration whereas R2* (¼1/T2*) or quantitative susceptibility maps are particularly sensitive to iron (Wharton and Bowtell, 2012) in deep gray matter structures but sensitive to both myelin and iron in cortical gray matter (Stüber et al, 2014;Wallace et al, 2016). Proton density maps, however, can be used to visualize macromolecular tissue volume (Mezer et al, 2013).…”
Section: Quantitative Mri and In-vivo Histology Using Mri (Hmri)mentioning
confidence: 99%